Zinc biofortification through seed nutri-priming using alternative zinc sources and concentration levels in pea and sunflower microgreens - Poudel, Pradip; Di Gioia, Francesco; Lambert, Joshua D.; Connolly, Erin L. (Frontiers in Plant Science, 2023)
Micronutrient deficiencies caused by malnutrition and hidden hunger are a growing concern worldwide, exacerbated by climate change, COVID-19, and conflicts. A potentially sustainable way to mitigate such challenges is the production of nutrient-dense crops through agronomic biofortification techniques. Among several potential target crops, microgreens are considered suitable for mineral biofortification because of their short growth cycle, high content of nutrients, and low level of anti-nutritional factors. A study was conducted to evaluate the potential of zinc (Zn) biofortification of pea and sunflower microgreens via seed nutri-priming, examining the effect of different Zn sources (Zn sulfate, Zn-EDTA, and Zn oxide nanoparticles) and concentrations (0, 25, 50, 100, and 200 ppm) on microgreens yield components, mineral content, phytochemical constituents such as total chlorophyll, carotenoids, flavonoids, anthocyanin, total phenolic compounds, antioxidant activity, and antinutrient factors like phytic acid. Treatments were arranged in a completely randomized factorial block design with three replications. Seed soaked in a 200 ppm ZnSO4 solution resulted in higher Zn accumulation in both peas (126.1%) and sunflower microgreens (229.8%). However, an antagonistic effect on the accumulation of other micronutrients (Fe, Mn, and Cu) was seen only in pea microgreens. Even at high concentrations, seed soaking in Zn-EDTA did not effectively accumulate Zn in both microgreens' species. ZnO increased the chlorophyll, total phenols, and antioxidant activities compared to Zn-EDTA. Seed soaking in ZnSO4 and ZnO solutions at higher concentrations resulted in a lower phytic acid/Zn molar ratio suggesting higher bioaccessibility of the biofortified Zn in both pea and sunflower microgreens. These results suggest that seed nutrient priming is feasible for en-riching pea and sunflower microgreens with Zn. The most effective Zn source was ZnSO4, followed by ZnO. The optimal concentration of Zn fertilizer solution should be selected based on fertilizer source, target species, and desired Zn-enrichment level.